Interfacial electronic coupling of ultrathin transition-metal hydroxide nanosheets with layered MXenes as a new prototype for platinum-like hydrogen evolution. Issue 12 (27th October 2021) - Li, Linlin; Yu, Deshuang; Li, Peng; Huang, Hongjiao; Xie, Dengyu; Lin, Chia-Ching; Hu, Feng; Chen, Han-Yi; Peng, Shengjie
Abstract : The well-designed hybrid electrocatalysts have been synthesized by anchoring ultrathin transition metal hydroxides on MXene nanosheets to boost the HER performance. Thanks to the unique architecture and synergistic effects, Co(OH)2 @MXene manifests unprecedented catalytic activity. Abstract : Metal hydroxides and oxides have emerged as fascinating materials and key structures for electrocatalysis however, they have rarely been investigated for the HER. Herein, we introduce unique transition-metal hydroxides@MXene (TMHs@MXene) hybrids, including Co(OH)2 @MXene, Ni(OH)2 @MXene, and FeOOH@MXene, with well-defined components and hierarchical sheet-like architectures for the alkaline HER. By virtue of their novel structure and the strong interfacial interactions between transition-metal hydroxides (TMHs) and MXene nanosheets, the obtained nanohybrids not only provide sufficient active sites and a robust structure, but also ensure favourable electrochemical kinetics and superior catalytic activity. Significantly, both theoretical calculations and the electrochemical test prove that the interfacial electronic coupling between the two different components could optimize the adsorption energy of water and hydrogen, thereby resulting in Pt-like catalytic activity including a low Tafel slope (31.7 mV dec −1 ), a small overpotential (21.0 mV@10 mA cm −2 ), and excellent stability for Co(OH)2 @MXene. As expected, an alkaline water electrolyzer was built using Co(OH)2 @MXene as the cathode for overall water splitting, which achieves a current density of 10 mA cm −2 at 1.46 V with outstanding stability over 100 h. Our discovery highlights the great potential of interfacial electronic coupling to optimize advanced electrocatalysts for application in energy-related fields.